Melastoma malabituin (Melastomataceae): a new species from northern Luzon, Philippines - Agcaoili, John Michael; Barcelona, Julie F.; Pelser, Pieter B. (Phytotaxa, 2020)
Melastoma malabituin is described and illustrated. This new species is currently only known from the municipalities of San Mariano and Echague, Isabela Province, Luzon, Philippines, where it is found in remnants of secondary lowland forests in the Sierra Madre mountain range. It is characterized by having densely pilose indumentum on young stems and petioles, penicillate trichomes on its hypanthium, and serrulate and ciliate petals with an apical penicillate emergence.